Club-based and non-club-based physiotherapists' views on the psychological content of their practice when treating sports injuries - Lafferty, M. E.; Kenyon, R.; Wright, C. J. (Research in Sports Medicine, 2008)
The aim of the present study was to explore whether there were any differences in the psychological content of practice between club-contracted and non-club-contracted physiotherapists when treating sports injuries. Eighty-seven certified physiotherapists (non-club contracted N = 42, club contracted N = 45) from the United Kingdom completed a modified version of the Athletic Training and Sport Psychology Questionnaire (ATSPQ). Results revealed significant between-group differences in psychological skills use and the importance of psychological skills knowledge. Non-club-contracted physiotherapists reported a higher use of improving social support and higher-order psychological skills (e.g., reducing depression, stress, and anxiety) and rated knowledge of these psychological skills to be more important whilst club-contracted physiotherapists reported a higher use of short-term goal settings. These findings suggest that non-club-based physiotherapists may approach the treatment of injured athletes in a different way to their club-based counterparts. Results suggest athletes treated outside of the club system may experience a different recovery process.